Uneven performance of Taiwan-born wage earners in the American and Canadian job market: Important roles of educational attainment and entry age - Kao-Lee Liaw; Ji-Ping Lin; Chien-Chia Liu (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2015)
For the Taiwan-born male and female wage earners in America and Canada, this paper attempts to find their wage gaps between the two host countries and to explain the wage gaps by three factors (educational attainment, the age at entering the host country, and the recency of the entry) in the context of current age. We apply an exponential regression model to the micro data of the 2005-2007 American Community Survey and the 2006 Canadian census. Predicted overall wage gaps are separated into two components: structural and compositional. [...]
Keywords: C18; C51; C87; J31; 330; Wage; Taiwan-born; Canada; America; Immigrants; Educational Attainment; Entry Age